Delays in diagnosis and treatment initiation for congenital cytomegalovirus infection - Why we need universal screening - Alifieraki, Styliani; Payne, Helen; Hathaway, Chantal; Tan, Rachel Wei Ying; Lyall, Hermione (Frontiers in Pediatrics, 2022)
Introduction: Congenital cytomegalovirus (cCMV) is the leading cause of neurodevelopmental and hearing impairment from in-utero infection. Late diagnosis results in limited treatment options and may compromise long-term outcome. Methods: A retrospective audit of infants with cCMV referred to a Tertiary Paediatric Infectious Diseases centre from 2012-2021. Data collected included timing of diagnostics, treatment initiation and reasons for delays. Results: 90 infants with confirmed cCMV were included, 46/90 (51%) were symptomatic at birth. Most common reasons for diagnostics in asymptomatic infants were failed newborn hearing screening (17/44, 39%) and antenatal risk-factors (14/44, 32%). Median age at cCMV diagnosis was 3 (range 0-68) and 7 (0-515) days, with median referral age 10 (1-120) and 22 (2-760) days for symptomatic and asymptomatic infants respectively. There was a significant risk of delay in diagnosis (>21 days) for asymptomatic infants [RR 2.93 (1.15-7.45); p=0.02]. Of asymptomatic infants who received treatment, 13/24 (54%) commenced it within 28 days of life, a significant delay in treatment compared to 30/36 (83%) symptomatic infants [RR 2.75 (1.18-6.43); p=0.02]. The commonest reason for delayed treatment initiation was delayed first diagnostic test for both symptomatic 4/6 (67%) and asymptomatic infants 9/11 (82%). Conclusions: Delays in diagnosis and treatment for cCMV are unacceptably frequent and significantly higher in asymptomatic infants. Our study highlights the need for increased awareness among healthcare professionals, reconsideration of age-targets for Newborn Hearing Screening, and research that addresses the barriers to implementation of universal screening, which would ultimately facilitate prompt diagnosis and management of all infants with cCMV.